2020
DOI: 10.1136/bmjqs-2019-010666
|View full text |Cite
|
Sign up to set email alerts
|

From kamishibai card to key card: a family-targeted quality improvement initiative to reduce paediatric central line-associated bloodstream infections

Abstract: BackgroundCentral line-associated bloodstream infections (CLABSIs) are major contributors to preventable harm in the inpatient paediatric setting. Despite multiple guidelines to reduce CLABSI, sustaining reliable central line maintenance bundle compliance remains elusive. We identified frontline and family engagement as key drivers for this initiative. The baseline CLABSI rate for all our paediatric inpatient units (January 2016–January 2017) was 1.71/1000 central lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…A recent study showed that involving a Patient and Family Advisory Board led to a completely different shape of random audits and involving families more actively in central line maintenance by helping them understand the safety practices aimed at preventing harm, resulted in sustained CLABSI reductions and a 97% compliance rate even 2 years following the intervention. 25 The table shows Patients with implanted cardiac devices (such as pacemakers) requested a 'one stop shop' for MRIs where devices could be reprogrammed and scans acquired at a single location and visit. This led to a complete service redesign that increased throughput to 20 times the national average in England, a wait time reduction from 60 to 15 days, and results that were sustained for 2 years.…”
Section: Modify Qi Interventions To Enhance Sustainabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study showed that involving a Patient and Family Advisory Board led to a completely different shape of random audits and involving families more actively in central line maintenance by helping them understand the safety practices aimed at preventing harm, resulted in sustained CLABSI reductions and a 97% compliance rate even 2 years following the intervention. 25 The table shows Patients with implanted cardiac devices (such as pacemakers) requested a 'one stop shop' for MRIs where devices could be reprogrammed and scans acquired at a single location and visit. This led to a complete service redesign that increased throughput to 20 times the national average in England, a wait time reduction from 60 to 15 days, and results that were sustained for 2 years.…”
Section: Modify Qi Interventions To Enhance Sustainabilitymentioning
confidence: 99%
“…Patients and caregivers then served as 'extended memory' that shared responsibility for ongoing central line maintenance and felt empowered to speak up. 25 (education & audits)…”
Section: Modify Qi Interventions To Enhance Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Patient personal support (eg, family, friends, personal caregiver) Unique insight into when a patient is "not right" or "a little off" in ways clinicians may miss and be signs of medical errors (eg, adverse drug events) or unexpected deterioration (eg, unresponsiveness to treatment) Leaders solicit and share family perspectives 21 Establish family-centred rounding and routines 13 Bedside coordinators to amplify patient voice 23 Localise PFACs to units and/or conditions 24 Boundary-spanning professionals (eg, chaplains, social workers) Elevate the social determinants and patient/ family voice regarding factors that could threaten patient safety Providing emotional and psychological support for the patient, family and team delivering care Leaders (publicly) recognise the value of chaplains and social workers to care quality and safety 20 Embed these professionals in routines (rounding) and roles (bedside coordinator, PFAC leader) that bridge patient and those delivering care [23][24][25] Create forums where they support direct care providers emotional and psychological needs (eg, processing trauma) 20 Created by the authors. PFAC, patient and family advisory committee.…”
Section: Research-based Practices To Embed In Care Teammentioning
confidence: 99%
“…As an example, as part of an improvement initiative to reduce paediatric central line-associated bloodstream infections (CLABSI), families were given cards explaining the elements of the intervention bundle and what can be done to prevent CLABSI in their child. 5 Given their direct involvement in the project, patients and families were appropriately acknowledged as contributors to the study. 4.…”
mentioning
confidence: 99%